Development of PBL-Based Chemistry E-Modules for Colloidal Systems - Sri Adelila Sari; Nurfadillah Syam Nasution (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2024)
Integrating digital learning tools has become increasingly important for enhancing student engagement and learning outcomes in the rapidly evolving educational landscape. This research aimed to assess the feasibility of a developed e-module and its impact on student learning outcomes. The development process followed the ADDIE Model, comprising five stages: Analysis, Design, Development, Implementation, and Evaluation. The instruments used included interview sheets, e-module validation sheets, student response questionnaires, and a 20-item test instrument. The e-module was validated by experts based on content, presentation, language, and graphic criteria, achieving an average validity score of 91.6%, indicating strong validity. Following validation, the e-module was implemented with 36 eleventh-grade Science Program (XI MIA) students at a high Islamic school in Medan during the 2023/2024 academic year. The results demonstrated a significant improvement in student learning outcomes, as evidenced by an N-gain score of 0.76, which falls within the high criteria. Additionally, student responses to the e-module were overwhelmingly positive, with an average approval rating of 87%, categorising their feedback as